A SURVEY OF EMPIRICAL STUDIES ON MANAGEMENT OWNERSHIP - Bahram Barzegar; Mahdi Salehi (Indonesian Management and Accounting Research, 2009)
This study reviews relationship between management ownership and firm performance with regard to empirical evidences. Although in the financial literature, management ownership is suggested for reduction of agency problem, there are contradictory view points on this suggestion. Some empirical studies show that increasing in equities of managements can be responsible to better alignment of the monetary incentives between the managers and other equity owners. In contrast, other studies support the entrenchment argument hypothesis. The hypothesis stats that increasing of management's equity can contribute to reduce financial performance and may it creates control problem, when level of management ownership is high. In disputation between the incentive alignment and entrenchment argument, combined argument and Stultz's integrated theory raise. These arguments which are integrated by other arguments show that corporate performance is a non-monotonous function of management ownership. In spite of the above arguments, some scholars believe that management ownership has a passive role in corporate governance, because of being a function of financial performance. However, others state that absolutely there is no relationship between management ownership and financial performance. In circumstances, perhaps a new combination of ownership alternative mechanisms can do work competently. Key words: Management Ownership, Agency Problem and Financial Performance